Ultrafast Fenton-like reaction route to FeOOH/NiFe-LDH heterojunction electrode for efficient oxygen evolution reaction. Issue 38 (27th September 2021) - Liang, Yan; Wang, Jun; Liu, Depei; Wu, Lin; Li, Taozhu; Yan, Shicheng; Fan, Qi; Zhu, Kai; Zou, Zhigang
Abstract : An industrial-scale time- and cost-effective route to produce a highly efficient and stable oxygen evolution reaction (OER) electrode is desirable and highly challenging. Abstract : An industrial-scale time- and cost-effective route to produce a highly efficient and stable oxygen evolution reaction (OER) electrode is desirable and highly challenging. Here, we have developed a minute-scale Fenton-like reaction to produce a three-dimensional (3D) FeOOH/NiFe-LDH heterojunction OER electrode by using industrial Ni foam as an Ni source to react directly with a Fenton-like reagent. The resulting 3D electrode, comprising a xlow-crystalline nano-scale FeOOH/NiFe-LDH heterojunction with high electrolyte-permeability, afforded a remarkable OER performances with an overpotential of 238 mV at 100 mA cm −2, a Tafel slope of 28.9 mV dec −1, and stable running over 700 h. Our results suggested that the fully maximized three-dimensional FeOOH/NiFe-LDH heterojunction interactions would be the origination of the high OER activity, exhibiting big prospects for industrial-scale applications.